Citrus Plants: A Model System for Unlocking the Secrets of NO and ROS-Inspired Priming Against Salinity and Drought - Molassiotis, Athanassios; Job, Dominique; Ziogas, Vasileios; Tanou, Georgia (Frontiers in Plant Science, 2016)
Plants treated with chemical compounds can develop an enhanced capacity to resist long after treatment to (a)biotic stress, a phenomenon known as priming. Evidence suggests that reactive oxygen species (ROS) and reactive nitrogen species (RNS) coordinately regulate plant stress responses to adverse environmental conditions; however the mechanisms underlying this function remain unknown. Based on the observation that pre-exposure of citrus (Citrus aurantium L.) roots to the NO donor sodium nitroprusside (SNP) or to H2O2 prior to NaCl application can induce acclimation against subsequent stress we characterized the changes occurred in primed citrus tissues using several approaches. Herein, using this experimental model system, we provide an overview of our current knowledge of the possible mechanisms associated with NO and H2O2 priming to abiotic stresses, most remarkably on salt and drought. The data and ideas presented here introduce six aspects of priming behaviour in citrus under abiotic stress that provide knowledge necessary to exploit priming syndrome in the context of sustainable agriculture.